Körperkoordinationstest Für Kinder (KTK) for Brazilian Children and Adolescents: Factor Analysis, Invariance and Factor Score - Moreira, João Paulo Abreu; Lopes, Mariana Calábria; Miranda-Júnior, Marcio Vidigal; Valentini, Nadia Cristina; Lage, Guilherme Menezes; Albuquerque, Maicon Rodrigues (Frontiers in Psychology, 2019)
The decrease in children motor competence, with a consequent reduction in the levels of physical activities and fitness, impacting health negatively, has affected children across countries. In addition to consistent intervention strategies, it is necessary to use appropriate instruments. The Körperkoordinationstest Für Kinder (KTK) is a reliable and low-cost motor coordination test used in several countries but lacking psychometric evidence for the Brazilian population. The present study investigates the factor structure of KTK for a Brazilian sample; and, compared four possibilities of calculating the factorial score of the test, precisely the sum of the scores, sum of the standard scores, weighted method, and the refined method. The participants of the study consisted of 565 volunteers (49.9% boys), from 5 to 10 (7.93 1.51) years of age, with a Body Mass Index (BMI) means of 17.04 ( 2.81).The results showed that the KTK factor structure was adequate to the model for the total sample, by sex, and by age groups. However, the results did not confirm the invariance between sexes and age groups. Besides, our result showed that the sum of the raw scores of the subtests could be used as the factor score method in KTK. In the end, we conclude that the KTK is a valid test to measure the motor coordination of Brazilian children and adolescents, with features that qualify it as a useful instrument both for research and for the practice.